2018
DOI: 10.2196/mhealth.8613
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Mobile Apps for Potential Drug-Drug Interaction Check: Systematic Review and Content Analysis Using the Mobile App Rating Scale (MARS)

Abstract: BackgroundGeneral consumers can now easily access drug information and quickly check for potential drug-drug interactions (PDDIs) through mobile health (mHealth) apps. With aging population in Canada, more people have chronic diseases and comorbidities leading to increasing numbers of medications. The use of mHealth apps for checking PDDIs can be helpful in ensuring patient safety and empowerment.ObjectiveThe aim of this study was to review the characteristics and quality of publicly available mHealth apps tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 51 publications
3
70
2
2
Order By: Relevance
“…The results obtained in the present study indicate that app engagement is the section with the lowest score with respect to functionality, esthetics, and information, in line with other MARS assessments of apps for food provision [ 38 ], checking for drug interactions [ 56 ], and drunk driving prevention [ 57 ], and the lack of interactive features influences the engagement quality of these apps. However, in a comparison of the 3 purposes of the included apps, the engagement section of the meal planner apps received higher quality scores than that of the food product and restaurant apps.…”
Section: Discussionsupporting
confidence: 86%
“…The results obtained in the present study indicate that app engagement is the section with the lowest score with respect to functionality, esthetics, and information, in line with other MARS assessments of apps for food provision [ 38 ], checking for drug interactions [ 56 ], and drunk driving prevention [ 57 ], and the lack of interactive features influences the engagement quality of these apps. However, in a comparison of the 3 purposes of the included apps, the engagement section of the meal planner apps received higher quality scores than that of the food product and restaurant apps.…”
Section: Discussionsupporting
confidence: 86%
“…The evaluation of these apps was performed using MARS. MARS has been successfully applied in recent years to evaluate apps that assist mindfulness development [22], heart failure symptom monitoring and self-management [23], weight management [24], palliative care among pediatric patients [25], epilepsy self-management [26], and drug-drug interaction checking [27]. Our evaluation demonstrated that the overall scores of our apps were comparable with those of apps in the other fields, with the median score of 3.70 (IQR 0.78).…”
Section: Discussionmentioning
confidence: 99%
“…However some of these apps provided good quality, accurate, and comprehensive information about potential DDIs while other apps does not conformed to high standards. This study also identified secondary features such as medication reminder, refill reminder, medication history tracking, and pill identification could help enhance the effectiveness of potential DDI apps [38]. A study found that utilizing clinical decision support software in older adults with cancer was beneficial for detecting DDIs however, variability existed with severity reporting.…”
Section: Strategies For Reducing and Preventing The Risk Of Drug Intementioning
confidence: 99%